Pengaruh Gaya Hidup dan Kualitas Produk terhadap Keputusan Mahasiswa di Kota Malang Membeli Handphone Merek iPhone dengan Brand Image sebagai Variabel Intervening - Zonnete Bryllian Dheo; Fathorrahman; Pradiani, Theresia (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS DR SOETOMO SURABAYA, 2023)
The various smartphone brands that are currently available are a form of information technology development, one of which is the iPhone. Ownership of an iPhone has been considered as one of the hallmarks of a luxurious and trendy lifestyle by Indonesian people, especially among young people and student collage. This study aims to analyze the effect of lifestyle and product quality on purchasing decisions and their effect on Brand Image as an intervening variable for student collage in Malang City. The population in this study were active student collage in Malang City with a sample of 100 students as respondents. The sampling technique used was purposive sampling and the data analysis method used was path analysis with the Sobel test using the SPSS 25 data processing application. The results showed that lifestyle and product quality had a significant effect on Brand Image. In addition, lifestyle, product quality and Brand Image have a significant effect on purchasing decisions. Lifestyle and product quality both have a significant effect on purchasing decisions through Brand Image